Growth patterns and control of deiffenbachia seguine (Jacq) schott - Mohd. Hazwan Fikri, Abdul Rashid (Universiti Malaysia Sarawak (UNIMAS), 2015)
The study was conducted to determine the growth pattern and distribution of biomass allocation of Dieffenbachia seguine (Jacq.) Schott in natural habitat at Kampung Terasi, Sadong Jaya Sarawak. The main parts of the plant were contributed to the biomass dry matter composed of stems, leaves, petioles and roots brought to the External Laboratory at Faculty of Resource Science and Technology University Malaysia Sarawak. Five quadrats were constructed in both open area and under tree canopy shading area. The total number of plants and total number of leaves in the open area was recorded as the highest compared to the under tree canopy shading area. The leaf area (LA) was recorded highest at under tree canopy shading area compared to the open area. While, the specific leaf area (SLA) and leaf area ratio (LAR) also recorded as highest in the under tree canopy shading area. The highest biomass partitioned was to the leaves and petiole in the shaded area while for open area the highest biomass partitioned to the roots and stems. D. seguine had a great potential for mass production of planting materials through stem cutting. The control of D. seguine with six different treatments of herbicide did not show 100% desiccation effects. The treatment of combination of 2,4-D dimethylamine with Metsulfuron methyl was recorded more effective to control D. seguine.